2013
DOI: 10.1002/chem.201300540
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Particle Spectroscopy on Large SAPO‐34 Crystals at Work: Methanol‐to‐Olefin versus Ethanol‐to‐Olefin Processes

Abstract: The formation of hydrocarbon pool (HCP) species during methanol-to-olefin (MTO) and ethanol-to-olefin (ETO) processes have been studied on individual micron-sized SAPO-34 crystals with a combination of in situ UV/Vis, confocal fluorescence, and synchrotron-based IR microspectroscopic techniques. With in situ UV/Vis microspectroscopy, the intensity changes of the λ=400 nm absorption band, ascribed to polyalkylated benzene (PAB) carbocations, have been monitored and fitted with a first-order kinetics at low reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
80
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 41 publications
(90 reference statements)
10
80
1
Order By: Relevance
“…In contrast, the lower ratio of mono‐aromatics versus poly‐aromatics in the methanol (A) and (E) feedstocks (Figure 5) suggests that catalyst deactivation likely occurs by pore blockage by poly‐cyclic molecules throughout the H‐SAPO‐34 crystal. Figure 7 shows a schematic representation of the hypothesized effect of feedstock impurities on catalyst deactivation, which is in line with previous findings by our group 43. This envisaged mechanism of deactivation is also supported by the relatively low absorbance of the active species (characterized by the absorption bands at 350 and 390 nm) if a methanol (E) feedstock is used compared with a methanol (U) feedstock (Figure 1 versus Figure 3, summarized in Figure 4).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…In contrast, the lower ratio of mono‐aromatics versus poly‐aromatics in the methanol (A) and (E) feedstocks (Figure 5) suggests that catalyst deactivation likely occurs by pore blockage by poly‐cyclic molecules throughout the H‐SAPO‐34 crystal. Figure 7 shows a schematic representation of the hypothesized effect of feedstock impurities on catalyst deactivation, which is in line with previous findings by our group 43. This envisaged mechanism of deactivation is also supported by the relatively low absorbance of the active species (characterized by the absorption bands at 350 and 390 nm) if a methanol (E) feedstock is used compared with a methanol (U) feedstock (Figure 1 versus Figure 3, summarized in Figure 4).…”
Section: Resultssupporting
confidence: 86%
“…In general, it can be said that fewer gas‐phase impurities lead to longer induction and active periods. However, the elongated induction period for methanol (E) with respect to methanol (A), containing less impurities, also suggests a competing pathway for ethanol‐to‐olefins conversion, which was previously noted by our group 43. That is, the ethanol‐to‐olefins (ETO) process leads to the selective formation of aromatics, or coke deposits, over olefins 2, 49, 50.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…30,31 Finally, secondary reaction products including less active poly-aromatic compounds are formed as can be seen in UV-Vis spectra of catalyst samples under MTO conditions. [32][33][34][35] This coke formation eventually leads to catalyst deactivation by pore 36 and/or site 37 blocking. It has been reported that the deactivation rate was substantially decreased by water addition to the feed.…”
Section: Introductionmentioning
confidence: 99%